Microdytes Balfour-Browne of India with description of three new species (Coleoptera: Dytiscidae: Hydroporinae) - Miller, Kelly B.; Wewalka, Günther (Zootaxa, 2010)
Three new species in the genus Microdytes Balfour-Browne (Coleoptera: Dytiscidae) are described from southwestern India: M. cameroni n. sp., M. svensoni n. sp. and M. whitingi n. sp. A key to the ten species of the genus Microdytes currently known from India is provided, and some new records of Indian Microdytes are given.